THE EVALUATION OF SUPRATROCHLEAR OSSEOUS MORPHOLOGY: AN EPIDEMIOLOGIC STUDY. Issue 3 (31st March 2019) - Onor, Gabriel; Mason, Bonnie; Farrow, Lutul
Introduction: Patellar instability can impede activities of daily life. The morphology of the femoral trochlea has significant involvement in maintaining patellofemoral joint stability. Trochlear dysplasia, or a shallow trochlear groove, has been implicated as a risk factor for recurrent patellar dislocation. A supratrochlear spur in the setting of existing trochlear dysplasia can generate further patellar instability. Trochleoplasty has been popularized by some surgeons for the treatment of recurrent patellar instability in the setting of significant trochlear dysplasia. Despite recommendation of trochleoplasty in treatment of patellar instability in the setting of trochlear dysplasia, much is unknown about the prevalence of trochlear dysplasia and supratrochlear spurs in the general population. The purpose of this study is to investigate the prevalence of supratrochlear spurs and trochlear dysplasia in the population and investigate the relationship between supratrochlear spurs and dysplastic femoral trochleae. Methods: This study was performed at the Cleveland Museum of Natural History, the Hamann Todd Human Osteological Collection. With over 4, 000 complete human skeletons, the Hamann Todd osteological collection at the Cleveland Museum of Natural History is the largest collection of osteological specimens with documented demographic data in the Western Hemisphere. We evaluated femora from over 1, 000 individuals aged 16-40 years. Each specimen was evaluated for the presence of trochlear dysplasia and supratrochlear spurs. We excluded skeletally immature specimens as well as specimens with visible signs of osteoarthritis or abnormal, bony deformity. The presence or absence of supratrochlear spurs was documented. Abnormal femoral trochleae were photographed in A/P, axial, and lateral views. The width and length of supratrochlear spurs were measured using digital calipers. Results: Of the 1, 148 specimens studied, 135 femora from 93 individuals were found to be dysplastic. Amongst these, 9 femora with trochlear dysplasia had supratrochlear spurs. The average age of individuals with dysplastic trochleae in this study was 32.86. Of the 93 specimens identified, 24 were female (25.8%). Additionally, 52% of individuals with dysplastic trochleae were white while 48% were black. Conclusions: There may be an association of supratrochlear spurs with trochlear dysplasia. Though 25.8% of individuals with dysplastic trochleae were female, it is important to note that the Hamann Todd Collection as a whole is 19% female.